If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + -41 = a + 21 Reorder the terms: -41 + 2a = a + 21 Reorder the terms: -41 + 2a = 21 + a Solving -41 + 2a = 21 + a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. -41 + 2a + -1a = 21 + a + -1a Combine like terms: 2a + -1a = 1a -41 + 1a = 21 + a + -1a Combine like terms: a + -1a = 0 -41 + 1a = 21 + 0 -41 + 1a = 21 Add '41' to each side of the equation. -41 + 41 + 1a = 21 + 41 Combine like terms: -41 + 41 = 0 0 + 1a = 21 + 41 1a = 21 + 41 Combine like terms: 21 + 41 = 62 1a = 62 Divide each side by '1'. a = 62 Simplifying a = 62
| P=90-2(19) | | F(x)=6(x+8)-3 | | 7r=3r | | 11+2b=15 | | 3s-75=s+15 | | 3=11-2x-3x+5 | | P(19)=90-2(19) | | z+87=2z | | 16+2q=12 | | N=-2+x | | -5=12(6x-2)+7x | | s^2+(4s+3)=y | | P(19)=90-2x | | 15-2/5f=-6 | | 19.2j+3(17.3j+4.57)=3(9.8j-2.38) | | X=-2+n | | 14-(X+8)=8X-3 | | 408=-8(10n+9) | | (5-4i)(2+6i)=0 | | 10=z^2+3z | | 0.33(2x-1)=0.5(3x+1) | | g-62=15 | | 16+24=-5(3x-8) | | 6(2x+1)=2x-6x | | -13s-5+5s=11s+2(-11s-16) | | 312.50=a+.25 | | 3y^2+21y=0 | | n=4+(n+1)(-5) | | 2s=2s+6 | | 4(2x+7)=-30+26 | | 6x+19=63 | | -300=5(8a+4) |